Strategi Inovatif dan Berkelanjutan dalam Mengatasi Dampak Kenaikan Harga Kedelai pada Produksi Tahu - Hanifah Arifatillah; Setyariningsih , Eny; M Syamsul Hidayat (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study analyzes the innovative and sustainable strategies implemented by CV. Alam Semi in responding to the increase in soybean prices, which has significantly affected tofu production. Soybeans, as the main raw material, create substantial financial pressure for medium-scale producers when prices rise, requiring adaptive and resilient strategies to ensure business continuity. Using a descriptive qualitative approach, this research applied SWOT analysis and the Miles and Huberman method to formulate practical strategies. The analysis produced an IFAS score of 3.20 and an EFAS score of 3.42, positioning the company in Quadrant I (aggressive strategy). Based on this position, CV. Alam Semi adopted several aggressive strategies, including modernization of the production process, product diversification, packaging improvement, and optimization of distribution channels to enhance competitiveness. In addition, sustainable strategies were integrated into business operations, focusing on energy efficiency, organic waste utilization to create added value, and community empowerment initiatives. These combined approaches enable the company to maintain profitability while also ensuring long-term resilience amid raw material price fluctuations. The integration of aggressive and sustainability-oriented strategies reflects a balanced response to both market challenges and environmental considerations. The findings demonstrate that innovation and sustainability are not mutually exclusive but can work synergistically to strengthen competitive advantage. This study provides practical implications for tofu producers and other small- to medium-scale food enterprises facing similar challenges, while also contributing academically by offering insights into strategy formulation in volatile market conditions. The results highlight the importance of aligning financial, operational, and social aspects to build a resilient and sustainable business model.